The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1051/0004-6361/201424523
|View full text |Cite
|
Sign up to set email alerts
|

AGN spiral galaxies in groups: effects of bars

Abstract: Aims. We explore properties of barred active spiral galaxies in groups and clusters selected from the Sloan Digital Sky Survey data release 7 (SDSS-DR7), with the aim of assessing the effects of bars on active galactic nuclei (AGN) and the role of the high density environment. Methods. We identified barred active galaxies that reside in groups and clusters by cross-correlating the total barred AGN sample with the SDSS-DR7 group catalog. With the goal of providing a suitable quantification of the effects of bar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 73 publications
(99 reference statements)
2
16
0
Order By: Relevance
“…Nevertheless the bar fraction versus mass relation, along with the well known color-mass relation (Consolandi et al, 2016), implies that there is an higher fraction of bars among more massive galaxies with redder total colors, although we stress that these are still star forming spiral galaxies. This is still consistent with previous works such as the one of Masters et al (2011), Alonso et al (2013), Alonso et al (2014) who consistently find an increasing barfraction in redder galaxies. I found a difference between the bar fraction evaluated among all LTGs (ty¿1) and the one that embraces lenticulars.…”
Section: The Colors Of Bars: Discussion and Conclusionsupporting
confidence: 93%
See 1 more Smart Citation
“…Nevertheless the bar fraction versus mass relation, along with the well known color-mass relation (Consolandi et al, 2016), implies that there is an higher fraction of bars among more massive galaxies with redder total colors, although we stress that these are still star forming spiral galaxies. This is still consistent with previous works such as the one of Masters et al (2011), Alonso et al (2013), Alonso et al (2014) who consistently find an increasing barfraction in redder galaxies. I found a difference between the bar fraction evaluated among all LTGs (ty¿1) and the one that embraces lenticulars.…”
Section: The Colors Of Bars: Discussion and Conclusionsupporting
confidence: 93%
“…If and how the bar fraction evolves across the cosmic time is still under debate (Jogee et al, 2004;Sheth et al, 2008) as well as the exact determination of the dependence of the bar frequency on stellar mass (especially at the faint end of the mass function) and on galaxy environment (Thompson, 1981;Marinova et al, 2012;Skibba et al, 2012;Lansbury et al, 2014;Alonso et al, 2014). For example, Masters et al (2012), Skibba et al (2012), Méndez-Abreu et al (2012), Gavazzi et al (2015) all consistently report a bar fraction that increases with increasing mass.…”
Section: Introductionmentioning
confidence: 99%
“…They tend to have a less luminous AGN and red color (Kim et al 2020a, for details). Alonso et al (2014) found that the enhancement of nuclear activity is notable in barred active galaxies located in higher-density environments using a massive galaxy sample, consistent with our result.…”
Section: Entangled Effects Of Environments and Barssupporting
confidence: 91%
“…It is worth noting that studies as the above implying that different AGN types do not interact in the same way with their environment represent potential issues to the so-called unification AGN model (Antonucci 1993;Urry & Padovani 1995), which suggests that all AGN are the same type of object viewed from a different angle. Alonso et al (2014) show that spiral galaxies hosting AGN in groups are more likely to be barred than their counterparts in the field. Similar results were presented by Coelho & Gadotti (2011), who found twice as many AGN among barred galaxies, as compared to their unbarred counterparts, for low mass bulges.…”
Section: Introductionmentioning
confidence: 93%